Post-flight confusion: does flying affect the brain?. (August 2020) - Rands, Gianetta; McCabe, Thomas; Imray, Chris
Abstract : This paper describes a condition termed post-flight confusion using anecdotal and clinical observations. It reviews research from the fields of aviation and altitude medicine and how this could apply to some physiological changes that happen during commercial flights. The collection of symptoms observed is similar to those of delirium. More research is needed to validate these observations, to identify the risks of flying for older people and to consider not only how to minimise these risks but whether this situation contributes to our knowledge about the aetiologies of delirium and dementias.